1993
DOI: 10.1099/00222615-39-4-255
|View full text |Cite
|
Sign up to set email alerts
|

A new Brevibacterium sp. isolated from infected genital hair of patients with white piedra

Abstract: Summary.A new aerobic gram-positive non-sporeforming bacillus has been isolated from infected genital hair of patients with white piedra in association with Trichosporon beigelii. This species has been characterised morphologically, nutritionally, by DNA base composition, cell-wall analysis and cellular fatty-acid profile on the basis of 14 isolates. The G + C content of DNA is 63-05 mol Yo. Cell walls possess meso-diaminopimelic acid (Type IV) and the sugars glucose, galactose, xylose and ribose ; mycolic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 15 publications
(1 reference statement)
0
28
0
2
Order By: Relevance
“…Brevibacterium casei, Brevibacterium epidermidis (Collins et al, 1983), Brevibacterium iodinum (Collins et al, 1980), Brevibacterium mcbrellneri (McBride et al, 1993), Brevibacterium otitidis (Pascual et al, 1996), Brevibacterium avium (Pascual & Collins, 1999), Brevibacterium paucivorans (Wauters et al, 2001) and Brevibacterium luteolum (Wauters et al, 2003;Euzéby & Tindall, 2004). Brevibacteria are isolated from dairy milk products, encountered in humans as commensals or opportunistic pathogens, are found to be residents of poultry and also occur in marine and terrestrial environments, as reported by Collins (1992) and Jones & Keddie (1986), and are available from public databases.…”
mentioning
confidence: 99%
“…Brevibacterium casei, Brevibacterium epidermidis (Collins et al, 1983), Brevibacterium iodinum (Collins et al, 1980), Brevibacterium mcbrellneri (McBride et al, 1993), Brevibacterium otitidis (Pascual et al, 1996), Brevibacterium avium (Pascual & Collins, 1999), Brevibacterium paucivorans (Wauters et al, 2001) and Brevibacterium luteolum (Wauters et al, 2003;Euzéby & Tindall, 2004). Brevibacteria are isolated from dairy milk products, encountered in humans as commensals or opportunistic pathogens, are found to be residents of poultry and also occur in marine and terrestrial environments, as reported by Collins (1992) and Jones & Keddie (1986), and are available from public databases.…”
mentioning
confidence: 99%
“…At the time of writing, the following 15 species with validly published names, in addition to the type species Brevibacterium linens, remain within the genus: Brevibacterium antiquum, B. aurantiacum, B. permense (Gavrish et al, 2004), B. avium (Pascual & Collins, 1999), B. casei, B. epidermidis (Collins et al, 1983), B. cerele (Ivanova et al, 2004), B. iodinum (Collins et al, 1980), B. luteolum (Wauters et al, 2003;Euzéby & Tindall, 2004), B. mcbrellneri (McBride et al, 1993), B. otitidis (Pascual et al, 1996), B. paucivorans (Wauters et al, 2001), B. picturae (Heyrman et al, 2004), B. sanguinis (Wauters et al, 2004) and B. samyangense (Lee, 2006). While most of the species were isolated from dairy products, clinical specimens, poultry and soils, a few were recovered from marine environments, such as algae and beach sediment, as reported previously (Ivanova et al, 2004;Lee, 2006).…”
mentioning
confidence: 99%
“…The cell morphology and culture characteristics are also different : cells of the new strains are stained evenly and they are short and plump, whereas those of B. mcbrellneri are somewhat irregular and thin. The glistening smooth or sticky colonies of the strains are in sharp contrast to the dry and crumbly colonies of B. mcbrellneri (McBride et al, 1993). Biochemically, the study strains can be further differentiated from B. mcbrellneri by the lack of casein hydrolysis.…”
Section: Resultsmentioning
confidence: 84%
“…Four species have been recognized in humans : Brevibacterium casei (Collins et al, 1983), Brevibacterium epidermidis (Collins et al, 1983), Brevibacterium mcbrellneri (McBride et al, 1993) and Brevibacterium otitidis (Pascual et al, 1996). Brevibacterium avium has been isolated from poultry (Pascual & Collins, 1999).…”
Section: Introductionmentioning
confidence: 99%